P3.449* The promise of estriol cream for prevention of vaginal infection in premenopausal women. (13th July 2013) - Dzuba, I. G.; Jones, H.; Ballagh, S. A.; Clark, W. H.; Hillier, S.; Irwin, T.; Marx, P.; Smith, S.; Veazey, R. S.; Winikoff, B.
Abstract : Background: Vaginal epithelium thins during the luteal phase of the menstrual cycle, increasing susceptibility to vaginal infection. Exogenous oestrogen thickens vaginal epithelium in ovariectomized monkeys and protects against SIV transmission. While topical oestrogen has beneficial effects on vaginal health in postmenopausal women, its effects in pre-menopausal women are uncertain. This randomised controlled trial evaluated thickening and maturation effects of estriol cream on vaginal epithelium and changes in microflora in premenopausal women. Methods: Eligible women made visits in follicular and luteal phases before and after randomization to estriol cream (1mg estriol/1ml cream) or matching placebo. Women applied 4mg cream 3 times weekly for approximately 6 weeks before follow-up visits. Vaginal biopsies were collected for analysis of epithelial thickness and cell layers. Swabs were collected for Gram stain (scored by Nugent's criteria) and for aerobic and anaerobic bacterial culture. Pearson's t-test was used to compare means, Fishers exact test to compare proportions, and generalised estimating equations to compare person-weeks of cream use to pre-cream person-weeks. Results: 102 eligible women were enrolled; 83% (85) completed the study. With estriol, average epithelial thickness increased (27.5 μm, 95% CI 9.7–45.4), as did transitional cell layers (1.3, 95% CI 0.6–2.0), compared to baseline, with no changes among placebo users. E. coli colonisation increased among placebo users compared to baseline (OR 4.9, 95% CI 2.7–8.9), but not among estriol users (OR 0.98, 95% CI 0.4–2.2). The presence of white blood cells decreased only with estriol cream relative to baseline (OR 0.25 95% CI 0.11–0.55). No serious adverse events were reported and adverse events did not differ by study group. Conclusion: Vaginally-applied estriol cream safely increases epithelial thickness in luteal phase, mitigates the E. coli colonisation associated with use of other vaginal products, and has favourable immunological effects. Estriol holds promise to enhance vaginal infection prevention.